Probiotic Cocktail Alleviates Intestinal Inflammation Through Improving Gut Microbiota and Metabolites in Colitis Mice - Zhu, Yefei; Xu, Yu; Wang, Xinyue; Rao, Leiping; Yan, Xuebing; Gao, Renyuan; Shen, Tongyi; Zhou, Yuan; Kong, Cheng; Zhou, Longxiang (Frontiers in Cellular and Infection Microbiology, 2022)
The modulation of gut microbiome has been widely suggested as a promising therapeutical strategy for inflammatory bowel disease (IBD). Here, we established a novel probiotic cocktail aiming to investigate its therapeutical role in colitis mice. During dextran sulfate sodium (DSS)-induce colitis, the mice were respectively treated with probiotic cocktail, healthy mice-donor fecal microbiota transplantation (FMT), or 5-aminosalicylic acid (5-ASA). The inflammatory responses were assessed by disease symptoms, serum inflammatory factors, and histological scoring. The intestinal barrier function was assessed by detecting tight junction proteins. Gut microbiota and its metabolites were further identified using 16S rDNA sequencing and liquid chromatograph mass spectrometer (LC-MS/MS). Compared with FMT and 5-ASA treatment, probiotic cocktail performed better in alleviating symptoms of colitis, decreasing disease activity score and mucosal inflammation. Probiotics cocktail also significantly decreased serum IL-17 level and increased JAM-1 expression in colon. The gut microbiota analysis confirmed that the beneficial effects of probiotic cocktail were attributed to increasing anti-inflammatory bacteria Akkermansia, Bifidobacterium and Blautia, and decreasing pro-inflammatory bacteria Parasutterella. The targeted metabolome analysis further indicated the increasing production of Bifidobacterium-related short-chain fatty acids (SCFAs) such as propanoic acid and isobutyric acid after probiotics treatment. Taken together, probiotic cocktail effectively alleviated intestinal inflammation through improving gut microbiota and metabolites in colitis mice, suggesting its great potential to be a novel therapeutical approach for IBD patients.